Glucose‐induced decrease of cystathionine β‐synthase mediates renal injuries. Issue 5 (17th April 2021) - Yu, Yanting; Xiao, Leijuan; Ren, Zhiyun; Zhu, Gangyi; Wang, Weiwan; Jia, Yutao; Peng, Ai; Wang, Xiaoyan
Abstract: Exogenous hydrogen sulfide (H2 S) protects kidneys from diabetic injuries in animal models. In order to explore the role of endogenous H2 S in diabetic nephropathy, we determined the renal H2S producing enzymes in vivo and in vitro. In diabetic mice, H2 S levels in blood and kidney were decreased while cystathionine β‐synthase (CBS), mainly located in mouse renal proximal convoluted tubules (PCT), was reduced selectively. In cultured mouse PCT cells treated with high glucose, CBS protein and activity was reduced while ubiquitinated CBS was increased, which was abolished by a proteasome inhibitor MG132 at 1 hour; high glucose drove CBS colocalized with proteasome 26S subunit ATPase6, indicating an involvement of ubiquitination proteasome degradation. At 48 hours, high glucose also selectively decreased CBS protein, concentration‐dependently, but increased the ubiquitination of CBS; silence of CBS by siRNA increased nitrotyrosine, a marker for protein oxidative injury. Nitrotyrosine was also increased by high glucose treatments. The increases of nitrotyrosine either by cbs‐siRNA or by glucose were restored by GYY4137, indicating that the H2 S donor may protect kidney from oxidative injury induced by CBS deficiency. In diabetic kidneys, ubiquitinated CBS and nitrotyrosine were increased but restored by GYY4137. The treatment also ameliorated albuminuria and renal morphologic changes in diabetic mice. Our findings suggest that high glucose induces reduction of renal CBS protein and activity in vivo and in vitro that is critical to the pathogenesis of diabetic kidney disease.